Verbal attacks on Ghanaian traditional leaders on an online news platform - Thompson, Rachel; Agbaglo, Ebenezer (Acta Scientiarum. Language and Culture, 2025)
The aim of this paper is to analyse verbal attacks targeting three prominent Ghanaian traditional leaders in comments on news articles published on GhanaWeb. The paper relies on appraisal theory, social actor analysis, and the theory of impoliteness to qualitatively analyse a number of purposively selected comments on the subject, published on the news website in 2022. The paper reports that these traditional leaders were verbally attacked on the basis of their capacity, truthfulness, propriety and seriousness. These attacks were based on the chiefs’ alleged failure to protect the land and natural resources from illegal mining, their engagement in partisan politics, and some criminal activities. The paper argues that as verbal attacks are not culturally permitted in Ghana, it is the anonymity of the news site that encourages these commenters to verbally attack the chiefs. This paper serves as a springboard for further research on verbal attacks, not only on the comment sections of news sites in other communities but on social media platforms as well.